60th Anniversary of Postgraduate School of Federal State-Financed Institution “Federal Centre for Animal Health” - Т. V. Zhbanova; Т. B. Nikeshina; N. А. Perevozchikova; N. А. Мarova (Ветеринария сегодня)
When the All-Union Foot-and-Mouth Disease Research Institute was founded in 1958, an active search for relevant specialists and researchers was organized with a view to recruiting them as staff members. In the early days of its establishment, the All-Union Foot-and-Mouth Disease Research Institute was mainly stuffed with the graduates of the Moscow Academy of Veterinary Medicine named after K. I. Skryabin and the Kharkov, Leningrad, Vitebsk Institutes of Veterinary Medicine. Later they were joined by the graduates of the University of Gorky, the Kazan and Ivanovo Institutes of Veterinary Medicine, the Vladimir Pedagogical Institute and many others. In 1963, the All-Union Foot-and-Mouth Disease Research Institute began to train research workers through postgraduate training programmes and thesis-based programmes. The leading scientists of the Institute were authorized by a decision of the Higher Attestation Commission of the USSR to provide academic supervision to postgraduate students. A specialized council for thesis defense started its activities in regard to Candidate of Science thesis defense in 1976 and in regard to Doctor of Science thesis defense – in 1996. The specialized council for Candidate of Science thesis defense comprised Candidates and Doctors of Sciences, staff members of the All-Union Foot-and-Mouth Disease Research Institute, as well as Doctors of Sciences from the All-Russian Research Institute of Veterinary Virology and Microbiology (VNIIVViM) (N. I. Arkhipov, I. F. Vishnyakov, V. M. Kolosov, N. A. Lagutkin, Yu. I. Petrov, G. A. Safonov, G. G. Yurkov). In 1996, the specialized council for Candidate of Science thesis defense was enlarged, and the following reputable scientists were invited to participate in its activities as its members: two Doctors of Sciences from the VNIIVViM (Ye. M. Khripunov, M. A. Dymin), four staff members of the VGNKI (K. N. Gruzdev, A. N. Panin, V. I. Ulasov, K. V. Shumilov), the staff members of the Veterinary Department of the Ministry of Agriculture of the Russian Federation (O. I. Sukharev) and the Peoples’ Friendship University of Russia (V. V. Makarov). The paper provides brief information on the training of scientific personnel for research and production laboratories of the institution, postgraduate school activities, thesis-based programmes, the council for Doctor of Science and Candidate of Science thesis defense.